HORMONE-POSITIVE HER2-NEGATIVE METASTATIC BREAST CANCER: DECISION MAKING IN REAL CLINICAL PRACTICE - L. Yu. Vladimirova; A. E. Storozhakova; T. A. Snezhko; L. K. Strakhova; N. A. Abramova; S. N. Kabanov; E. A. Kalabanova; N. Yu. Samaneva; Ya. V. Svetitskaya; A. V. Tishina (Южно-Российский онкологический журнал)
Breast cancer (BC) is the most common female cancer and the first leading cause of cancer death in women. Luminal phenotypes represent about 70% of this disease. Treatment for metastatic hormone‑dependent HER2‑negative breast cancer in most cases involves various lines of endocrine therapy since their sequential use improves overall and relapse‑free survival while maintaining a high quality of life. Disease progression during such therapy may be associated with the development of primary or secondary resistance to the treatment. The reason for the secondary resistance is both a mutation of receptors for steroid hormones and activation of new signaling pathways. The study of these mechanisms has led to the creation of highly effective drug combinations for the treatment of hormone‑positive HER2‑negative metastatic breast tumors. To date, clinical trials of three agents from the group of cyclin‑dependent kinases has been developed and successfully completed: palbociclib, ribociclib and abemaciclib. These agents in combination with non‑steroidal aromatase inhibitors or estrogen receptor antagonists in randomized clinical trials increased direct treatment efficacy, overall survival and progression‑free survival rates. Clinical case of a menopausal patient with metastatic hormone‑positive HER2‑negative breast cancer with visceral metastases who received successive chemotherapy and a combination of the highly selective oral kinase inhibitor CDK4\6 ribocyclib with the aromatase inhibitor letrozole allowed to achieve a response to therapy for 27 months with CR for 8 months. The safety profile was satisfactory; side effects included grade 2 neutropenia, grade 1 arthralgia, grade 1 hyperglycemia and grade 1 increase in urea which did not had an adverse effect on the patient’s quality of life.